Advances in the management of rheumatoid arthritis. Issue 3 (August 2015) - Dale, James
Modern early rheumatoid arthritis strategies are usually based upon a number of important overarching principles: 1. early diagnosis facilitates early commencement of disease modifying anti-rheumatic therapy; 2. early commencement of treatment reduces the long-term risk of erosive damage and functional decline; 3. composite disease activity measures should be used to quantify global rheumatoid arthritis disease activity; and 4. therapy should be intensified until a predefined disease activity target has been achieved. A substantial minority of rheumatoid arthritis patients (approximately 40%) will experience an adequate response to methotrexate monotherapy; however, the remainder may require disease modifying anti-rheumatic combination therapy, and/or biologic therapy, to achieve disease activity targets. Importantly, short term trials of methotrexate monotherapy do not appear to disadvantage outcomes provided treatment continues to be intensified if disease activity targets are not achieved.